Perencanaan Pajak untuk UMKM - Yessica Amelia; Ngadi Permana; Evlin Chadra Rita (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2021)
MSMEs (Micro, Small, and Medium Enterprises) play a vital role in the national economy, yet they face significant challenges in sustaining their businesses during the COVID-19 pandemic. Effective tax planning can assist MSMEs in managing their tax obligations and taking advantage of government-provided incentives. However, tax planning must also consider other aspects such as accounting, legal frameworks, business models,and tax implications. In light of these considerations, this community service activity aims to explore tax planning strategies that can help MSMEs fulfill their tax obligations amid business challenges posed by the COVID-19 pandemic. This activity also serves as a platform for universities to actively support the government in disseminating tax regulations to the public, especially MSME operators. The event was conducted as an online seminar (webinar) with participants from MSME operators, students, academic scholars, and the general public from various regions in Indonesia.